Knowledge, Attitude and Practice Toward COVID-19 Among the Public in the Kingdom of Saudi Arabia: A Cross-Sectional Study - Mohammed K. Al-Hanawi; Khadijah Angawi; Noor Alshareef; Ameerah M. N. Qattan; Hoda Z. Helmy; Yasmin Abudawood; Mohammed Alqurashi; Waleed M. Kattan; Nasser Akeil Kadasah; Gowokani Chijere Chirwa; Gowokani Chijere Chirwa; Omar Alsharqi (Frontiers Media S.A., 2020)
Background: Saudi Arabia has taken unprecedented and stringent preventive and precautionary measures against COVID-19 to control its spread, safeguard citizens and ensure their well-being. Public adherence to preventive measures is influenced by their knowledge and attitude toward COVID-19. This study investigated the knowledge, attitudes, and practices of the Saudi public, toward COVID-19, during the pandemic.Methods: This is a cross-sectional study, using data collected via an online self-reported questionnaire, from 3,388 participants. To assess the differences in mean scores, and identify factors associated with knowledge, attitudes, and practices toward COVID-19, the data were run through univariate and multivariable regression analyses, respectively.Results: The majority of the study participants were knowledgeable about COVID-19. The mean COVID-19 knowledge score was 17.96 (SD = 2.24, range: 3-22), indicating a high level of knowledge. The mean score for attitude was 28.23 (SD = 2.76, range: 6-30), indicating optimistic attitudes. The mean score for practices was 4.34 (SD = 0.87, range: 0-5), indicating good practices. However, the results showed that men have less knowledge, less optimistic attitudes, and less good practice toward COVID-19, than women. We also found that older adults are likely to have better knowledge and practices, than younger people.Conclusions: Our finding suggests that targeted health education interventions should be directed to this particular vulnerable population, who may be at increased risk of contracting COVID-19. For example, COVID-19 knowledge may increase significantly if health education programs are specifically targeted at men.